Influence of Age, Sex and Anthropometry on Inspiratory Flow Rates of Patients with Chronic Obstructive Pulmonary Disease - Adetiloye, Adebola; Akor, Alexander; Awopeju, Olayemi; Adewole, Olufemi; Badero, Olurotimi; Erhabor, Gregory (International Journal of Innovative Research in Medical Science, 2024)
Introduction: Chronic Obstructive Pulmonary Disease (COPD) affects millions of people with increasing global prevalence, morbidity and mortality. Inhaled medications are central to the management of COPD. Therefore, understanding the minimum Peak Inspiratory Flow (PIF) requirements for inhaler devices is vital for optimal drug delivery. This study assessed PIF in patients with COPD compared with controls and, the influence of age, sex and anthropometric measurements on PIF. Methodology: A total of 150 subjects (75 patients with stable COPD, and 75 controls) participated in the study. Demographic and anthropometric data were collected from the study participants. Peak inspiratory flow was assessed using the In-check peak flow meter. Lung function was assessed by spirometry. In all the statistical tests, a p value of <0.05 was considered significant. Results: The control group had higher PIF than COPD group. All of the COPD patients had clinically effective PIF for Clickhaler, Diskus, Easibreathe, and pMDI. Majority of the COPD patients had clinically effective PIF for Turbohaler, and Autohaler. The mean PIF of male patients with COPD was significantly greater than that of females for Turbohaler. For the COPD group, there was a significant negative correlation between PIF and age for Diskus, Autohaler and Easibreathe. Significant positive correlation was also noted between PIF and weight for turbohaler, autohaler and easibreathe. Conclusion: Majority of COPD patients utilizing dry powder inhalers (DPIs) are able to generate effective PIF. Increasing age, female gender, low body weight and low BMI may contribute to low PIF.